Pretomanid-resistant tuberculosis. Issue 5 (May 2023) - Koehler, Niklas; Andres, Sönke; Merker, Matthias; Dreyer, Viola; John, Agnieszka; Kuhns, Martin; Krieger, David; Choong, Eva; Verougstraete, Nick; zur Wiesch, Pia Abel; Wicha, Sebastian G.; König, Christina; et al.
Highlights: Moxifloxacin daily doses of 2400 mg were tolerated over several months. M. tuberculosis drug resistance could be overcome by a high-dose treatment regimen. No occurrence of cardiac AEs despite high doses of QTc interval prolonging drugs. No eradication of M. tuberculosis despite longstanding culture conversion. Development of pretomanid resistance on an insufficient treatment regimen.